2008
DOI: 10.2337/db08-0031
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Bone Marrow–Derived Mesenchymal Stem Cells Improves Diabetic Polyneuropathy in Rats

Abstract: OBJECTIVE-Mesenchymal stem cells (MSCs) have been reported to secrete various cytokines that exhibit angiogenic and neurosupportive effects. This study was conducted to investigate the effects of MSC transplantation on diabetic polyneuropathy (DPN) in rats.RESEARCH DESIGN AND METHODS-MSCs were isolated from bone marrow of adult rats and transplanted into hind limb skeletal muscles of rats with an 8-week duration of streptozotocin (STZ)-induced diabetes or age-matched normal rats by unilateral intramuscular inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
150
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 62 publications
(51 reference statements)
7
150
1
Order By: Relevance
“…104 Similarly, bone marroweMSC and ASC transplants have been tested for the modulation of diabetic nephropathy and for the treatment of nonhealing diabetic wounds resulting from neuropathy and microvasculopathy. 14,105,106 This section details the various approaches of using autologous stem cells for treating diabetic complications.…”
Section: Treating Diabetic Complicationsmentioning
confidence: 99%
“…104 Similarly, bone marroweMSC and ASC transplants have been tested for the modulation of diabetic nephropathy and for the treatment of nonhealing diabetic wounds resulting from neuropathy and microvasculopathy. 14,105,106 This section details the various approaches of using autologous stem cells for treating diabetic complications.…”
Section: Treating Diabetic Complicationsmentioning
confidence: 99%
“…Several animal studies have addressed this question. They have been clear indications that ischaemia caused or aggravated by diabetes have been improved by stem cells [21,22].…”
Section: Stem Cell Treatment In Critical Limb Ischaemiamentioning
confidence: 99%
“…These cells were also chosen by Shibata et al for their ability to differentiate into a wide variety of cell types and to secrete cytokines, such as vascular endothelial growth factor and basic fibroblast growth factor. 20 Kim et al used MSCs since recent research has suggested that these stem cells promote neurotrophic factors and that loss of neurotrophic factors might be partly responsible for diabetic neuropathy. 12 Naruse et al instead used marrow mononuclear cells and mentioned that an advantage of these cells was that they are easily acquired.…”
Section: Spinal Cord Injurymentioning
confidence: 99%